Novel pulp capping material based on sodium trimetaphosphate: synthesis, characterization, and antimicrobial properties - Franzin, Nayara Rodrigues Sartori [UNESP]; Sostena, Michela Melissa Duarte Seixas [UNESP]; Santos, Alailson Domingos Dos; Moura, Marcia Regina [UNESP]; Camargo, Emerson Rodrigues de; Hosida, Thayse Yumi [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Moraes, João Carlos Silos [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVES: To evaluate the mechanical, physicochemical, and antimicrobial properties of four different formulations containing micro- or nanoparticles of sodium trimetaphosphate (mTMP and nTMP, respectively). METHODOLOGY: Four experimental groups were used in this investigation: two mTMP groups and two nTMP groups, each containing zirconium oxide (ZrO2), and solution containing either chitosan or titanium oxide (TiO2) nanoparticles (NPs). Setting time, compression resistance, and radiopacity were estimated. The agar diffusion test was used to assess the antimicrobial activity of the formulations against five different microbial strains: Streptococcus mutans, Lactobacillus casei, Actinomyces israelii, Candida albicans, and Enterococcus faecalis. Parametric and nonparametric tests were performed after evaluating homoscedasticity data (p<0.05). RESULTS: From the properties evaluated, nTMP cements required less setting time and showed greater resistance to compression. Cements containing TiO2 showed greater radiopacity for both nTMP and mTMP. All four cement formulations showed antimicrobial activity against S. mutans and L. casei. CONCLUSION: Formulations containing nTMP have shorter setting times and higher compressive strength, and those with TiO2 nanoparticles showed antimicrobial activities. Clinical relevance: The cement containing nTMP, ZrO2, and TiO2 could be an alternative material for protecting the pulp complex.